Eclâmpsia: fatores determinantes em um grupo de mulheres, atendidas em uma maternidade pública - LOPES, Leyla Santiago (2019)
This paper seeks to understand the determinants of health, eclampsia prevalent in a group of women, by identifying the predominant factors of the disease, knowledge of the socio-economic, cultural and reproductive health of respondents. To this end, we carried out a study, descriptive, quantitative, exploratory, sustained in the theoretical framework of hypertensive disorders in the manifestation of eclampsia and health education. Quantitative analysis of observed data points to the fact that most respondents do not perform paid, contributing to the worsening economic conditions and family for any consequences arising out of them, poor education has great influence on the worsening economic conditions of families, the difficulty access to formal education and little access to information, exposure to vulnerability and morbidity from preventable diseases such as preeclampsia Considering that most are recent grads in the state, the expectation is that lower adherence to prenatal care, is a function of difficulty of access and less likely to obtain adequate health care quality and quantity. The finding that the vast majority had complications in pregnancy and a small number had the appropriate number of visits during the prenatal period, leads to infer that a series of factors identified in this study contributed to the occurrence of eclampsia in the population studied. In contrast, we suggest the implementation of educational activities, such as major weapon for impact and change the frame now identified among the clientele of the Unified Health System.